A clean and membrane-free chlor-alkali process with decoupled Cl2 and H2/NaOH production - Hou, Mengyan; Chen, Long; Guo, Zhaowei; Dong, Xiaoli; Wang, Yonggang; Xia, Yongyao (Nature communications, 2018)
Existing chlor-alkali processes generally use asbestos, mercury or fluorine-containing ion-exchange membranes to separate the simultaneous chlorine production on the anode and hydrogen production on the cathode, and form sodium hydroxide in the electrolyte. Here, using the Na + de-intercalation/intercalation of a Na 0.44 MnO 2 electrode as a redox mediator, we decouple the chlor-alkali process into two independent steps: a H 2 production step with the NaOH formation in the electrolyte and a Cl 2 production step. The first step involves a cathodic H 2 evolution reaction (H 2 O → H 2 ) and an anodic Na + de-intercalation reaction (Na 0.44 MnO 2 → Na 0.44− x MnO 2 ), during which NaOH is produced in the electrolyte solution. The second step depends on a cathodic Na + intercalation reaction (Na 0.44− x MnO 2 → Na 0.44 MnO 2 ) and an anodic Cl 2 production (Cl → Cl 2 ). The cycle of the two steps provides a membrane-free process, which is potentially a promising direction for developing clean chlor-alkali technology. The chlor-alkali process is an important industrial process to make commodity chemicals; however, it usually requires the use of dangerous chemicals as membrane material. Here, the authors demonstrate clean, membrane-free chlor-alkali electrolysis, where chlorine evolution and hydrogen/sodium hydroxide production are completely decoupled.